Antibiotics and bioactive natural products in treatment of methicillin resistant Staphylococcus aureus: A brief review - Kali, Arunava (Pharmacognosy Reviews)
Infections caused by Staphylococcus aureus strains with Methicillin resistance are associated with increased mortality and morbidity, aggressive course, multiple drug resistance and hospital outbreaks. Several first and second line antibiotics are rapidly becoming ineffective for treatment due to emergence of resistance. Extracts of medicinal plants are rich source of unique phytochemicals. Plants used in traditional medicine have been reported to have significant anti‑MRSA activity. The objective of this review is to provide a brief overview of antibiotics as well as anti‑MRSA natural products and their future prospect.
Keywords: Methicillin resistant Staphylococcus aureus (MRSA); phytochemicals; plant extracts